Open-Source Urbanism: Creating, Multiplying and Managing Urban Commons - Karin Bradley (Footprint)
Within contemporary architecture and urbanism there is marked interest in urban commons. This paper explores the creation of temporary urban commons, or, more specifically, what can be called ‘open-source urbanism’. Citing two practices – urban commons initiated by Atelier d’architecture autogérée in Paris, and Park(ing) Day initiated by San Francisco-based Rebar – I argue that these practices can be understood as open-source urbanism since their initiators act as open-source programmers, constructing practice manuals to be freely copied, used, developed and shared, thus producing self-managed commons. Although this tradition of ‘commoning’ is not new, it is currently being reinvented with the use of digital technologies. Combining Elinor Ostrom’s analysis of self-managed natural resource commons with Yochai Benkler’s assertion that commons-based peer production constitutes a ‘third mode of production’ that lies beyond capitalism, socialism and their blends, I argue that open-source urbanism critiques both government and privately-led urban development by advancing a form of postcapitalist urbanism.